2023
DOI: 10.1007/s10126-023-10252-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Knock-down of mstn Encoding Myostatin Improves Muscle Quality of Nile Tilapia (Oreochromis niloticus)

Qingchun Wang,
Yue Yan,
Yifan Tao
et al.

Abstract: Myostatin (encoded by mstn) negatively regulates skeletal muscle mass and affects lipid metabolism. To explore the regulatory effects of mstn on muscle development and lipid metabolism in Nile tilapia (Oreochromis niloticus), we used antisense RNA to transcriptionally knock-down mstn. At 180 days, the body weight and body length were significantly higher in the mstn-knock-down group than in the control group (p < 0.05). Additionally, fish with mstn-knock-down exhibited myofiber hyperplasia but not hypertrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the mstn mutations caused a decreased lipid mass in mammals such as mice, cattle, and sheep [ 25 , 26 ]. In contrast, gene disruption or knockdown of mstn induced an increase in lipid content of skeletal muscle in some fish species, such as zebrafish ( Danio rerio ), loach ( Misgurnus anguillicaudatus ), and Nile tilapia [ [27] , [28] , [29] ]. MSTN plays two distinct roles: promoting adipogenesis [ 30 ] and inhibiting adipogenesis [ 31 ], however, its specific function in adipogenesis is currently controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the mstn mutations caused a decreased lipid mass in mammals such as mice, cattle, and sheep [ 25 , 26 ]. In contrast, gene disruption or knockdown of mstn induced an increase in lipid content of skeletal muscle in some fish species, such as zebrafish ( Danio rerio ), loach ( Misgurnus anguillicaudatus ), and Nile tilapia [ [27] , [28] , [29] ]. MSTN plays two distinct roles: promoting adipogenesis [ 30 ] and inhibiting adipogenesis [ 31 ], however, its specific function in adipogenesis is currently controversial.…”
Section: Discussionmentioning
confidence: 99%